2012
DOI: 10.4028/www.scientific.net/amm.229-231.503
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Model of the Primary Shear Zone for Orthogonal Machining

Abstract: A new modified model based on the non-parallel primary shear zone is presented in this paper. Experiments showed that the primary shear zone in cutting process wasn’t an absolutely parallel-sided zone. In fact, there are small inclined angles in the primary shear zone. Therefore, in this paper, a correction coefficient is proposed to predict cutting forces exactly. The coordinate mapping approach is adopted to obtain the correction coefficient and the software MATLAB is utilized to predict cutting forces. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the process of transforming the parallel plane shear zone to the non-parallel plane shear zone, in order to realize the calculation of the shear strain rate at each point in the shear zone, the value of |J| needs to be calculated. In the derivation process, Zhou [14] took the value of |J| at the center of gravity of the quadrilateral CDFE as the value of |J| at any point in the entire shear region:…”
Section: Proof That |J| Is Not a Constantmentioning
confidence: 99%
See 2 more Smart Citations
“…In the process of transforming the parallel plane shear zone to the non-parallel plane shear zone, in order to realize the calculation of the shear strain rate at each point in the shear zone, the value of |J| needs to be calculated. In the derivation process, Zhou [14] took the value of |J| at the center of gravity of the quadrilateral CDFE as the value of |J| at any point in the entire shear region:…”
Section: Proof That |J| Is Not a Constantmentioning
confidence: 99%
“…`By analyzing the metallography from orthogonal cutting on carbon steel and aluminum alloy workpiece and the relationship between shear strain and shear angle, Jesper [13] found that the two boundaries of shear zone (the initial shear plane and ultimate shear plane) are not parallel, and the initial shear plane and the ultimate shear plane have an inclination of about 0° to 9° relative to the main shear plane. On the basis of this, Zhou [14] applied the coordinate transformation method to the unequal division shear zone model, which is based on parallel shear planes, and cleverly obtained the formula of non-parallel shear zone model from a calculation formula of the unequal division shear zone model by using a set of transformation matrices. Then, the solution of the cutting force and cutting thrust of the non-parallel shear zone model is obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation